Chemical Synthesis of the Anti‐COVID‐19 Drug Remdesivir. Issue 12 (8th December 2021) - Wang, Mo; Zhang, Lu; Huo, Xiaohong; Zhang, Zhenfeng; Zhang, Wanbin
Abstract: Remdesivir has become an important compound for the treatment of COVID‐19. Here, we describe the catalytic asymmetric synthesis of this anti‐COVID‐19 drug. First, the P ‐racemic phosphoryl chloride is synthesized in a facile procedure. Then, it is possible to obtain the protected remdesivir via the organocatalytic asymmetric phosphorylation of protected nucleoside GS441524 with P ‐racemic phosphoryl chloride catalyzed by chiral bicyclic imidazole. Finally, remdesivir is easily prepared by deprotection. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of 2‐ethylbutyl (chloro(phenoxy)phosphoryl)‐L ‐alaninate rac ‐4 Basic Protocol 2 : Synthesis of chiral bicyclic imidazole Ad‐DPI Basic Protocol 3 : Synthesis of remdesivir